East Timor development challenges for the word's newest nation - Hill, Hal 1948-; Saldanha, Joao Mariano de Sousa 1963- (ISEAS current economic affairs series, 2001)
Looking at East Timor's economic development, this book covers macroeconomics and international economic relations, agriculture and the rural economy, finance and infrastructure, social policy, political and legal institutions and lessons from international experience.